INFLUENCE OF SINTERING HOLDING TIME ON THE MECHANICAL PROPERTIES AND MICROSTRUCTURE OF TITANIUM ALLOYED BY 1, 3, 5 WT% COPPER SINTERED ALLOYS WITH 40KN COMPACTION PRESSURE - SETIAWAN TANUWIJAYA (NIM : 12514019), ANGGIAN
Bacterial infection has become a major cause that lead to an implant failure over the last few years. The high cost and risk involved in treatment procedure demands for another preventive measure to be developed. One of the methods thatÃ‚Â’s being developed to prevent a bacterial infection to occurs is to bestow anti bacterial properties in the implantÃ‚Â’s material itself. Copper, as a metal with proven antibacterial properties, is found to be able to bring the aforementioned properties even when used as an alloying element. This results in a budding interest to alloy copper into titanium, which is a commonly used material for an implant, to bestow antibacterial properties to an implant. In this research, the mechanical properties of several sintered Ti-Cu alloys with varying fabrication parameter are put into test. Ti-Cu alloys are made by means of powder metallurgy with varying copper content of 1, 3, and 5% total weight. The mixture of powder then being mixed in a planetary ball mill for 1 hour, and then compacted into a cylinder of 1 cm diameter with 0.2 cm and 1.7 cm height. The specimens are then heated to 950 centigrade with varying duration of 2, 4 and 8 hours under inert atmosphere. A metallography of formed phase then done by optical and electron microscope with aid of EDS analysis. The hardness of the material is tested by Vickers Hardness methods, while the strength of the material is tested following ASTM E09 recommendation. The Ti-Cu sintered alloys were found to contained α-Ti and Ti2Cu phases, in which a eutectic structure is formed by a mixture of lamellar and granular structure. The hardest sample is found to be Ti-3Cu alloys with 4 hours sintering duration with Vickers number of 511.4. The highest compressed strength recorded is 1707.89 MPa belongs to Ti-1Cu alloys with 4 hours sintering time. The highest observable pore area belongs to Ti-5Cu alloys with 2 hours sintering time. An observation of the fracture surface with electron microscopes concludes that the sample undergoes a brittle transgranular failure, and x-ray mapping pointed out that the fracture surface is rich in copper.